A blueprint for general‐case procedures illustrated by teaching adolescents with autism spectrum disorder to use a chip‐debit card. (27th May 2020) - Milata, Eileen M.; Reeve, Sharon A.; Reeve, Kenneth F.; Dickson, Chata A.
Abstract: Individuals diagnosed with autism spectrum disorder (ASD) often respond poorly to novel stimulus combinations and may have difficulty discriminating across critical and noncritical stimulus dimensions without direct teaching. General‐case procedures and multiple‐exemplar training have been effectively used to address this deficit. In the current study, the experimenters outlined general‐case procedures with video modeling, prompting and reinforcement to teach three adolescents with ASD a generalized repertoire of using a chip‐debit card. A multiple‐probe across participants design demonstrated the effectiveness of these procedures. All participants acquired the skill, responding generalized from simulated teaching materials to four novel automatic payment machines, and maintained 4 weeks following teaching. Implications of using these general‐case procedures as a blueprint for future researchers to reference when teaching individuals with ASD a generalized repertoire of any skill are discussed.